Review of Occupational Health and Safety Organization in Expanding Economies: The Case of Southern Africa - Moyo, Dingani; Zungu, Muzimkhulu; Kgalamono, Spoponki; Mwila, Chimba D. (Ubiquity Press, 2022)
Globally, access to occupational health and safety (OHS) by workers has remained at very low levels. The organization and implementation of OHS in South Africa, Zimbabwe, Zambia, and Botswana has remained at suboptimal levels. Inadequacy of human resource capital, training, and education in the field of OHS has had a major negative impact on the improvement of worker access to such services in expanding economies. South Africa, Zimbabwe, Zambia, and Botswana have expanding economies with active mining and agricultural activities that pose health and safety risks to the working population. Methods: A literature review and country systems inquiry on the organization of OHS services in the 4 countries was carried out. Because of the infancy and underdevelopment of OHS in southern Africa, literature on the status of this topic is limited. Results: In the 4 countries under review, OHS services are a function shared either wholly or partially by 3 ministries, namely Health, Labor, and Mining. Other ministries, such as Environment and Agriculture, carry small fragments of OHS function. The 4 countries are at different stages of OHS legislative frameworks that guide the practice of health and safety in the workplace. Inadequacies in human resource capital and expertise in occupational health and safety are noted major constraints in the implementation and compliance to health and safety initiatives in the work place. South Africa has a more mature system than Zimbabwe, Zambia, and Botswana. Lack of specialized training in occupational health services, such as occupational medicine specialization for physicians, has been a major drawback in Zimbabwe, Zambia, and Botswana. Discussion: The full adoption and success of OHS systems in Southern Africa remains constrained. Training and education in OHS, especially in occupational medicine, will enhance the development and maturation of occupational health in southern Africa. Capacitating primary health services with basic occupational health knowledge would be invaluable in bridging the current skills deficit. Introducing short courses and foundational tracks in occupational medicine for general medical practitioners would be invaluable.